Some approaches to the assessment of the socio-economic consequences of restructuring of regional transport infrastructure - M. V. Zhukov (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2014)
To assess the integrated impact of the transport and infrastructure projects on the regional socio-economic situation the author proposes to use an universalized methodical approach. This approach allows to take into account both direct (activation) and countervailing indicators characterizing the possibilities of containment of transport limitations on socio-economic development of the territories of various ranks.